Development of LKPD in the Context of Tabut Culture with a STEAM Approach to Facilitate Numeracy Literacy - Muthia Maghfira; Ristontowi Ristontowi; Winda Ramadianti (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Numeracy literacy skills are basic competencies that need to be developed in junior high school (SMP) students in the 21st century. However, mathematics learning in schools has not yet linked the concept of mathematics to the cultural context in daily life. This research aims to develop Student Worksheets (LKPD) in the Context of Tabut Culture with a valid and practical STEAM approach to facilitate students' numeracy literacy. This research uses the Research and Development (R&D) method with a 4D development model comprising define, design, and develop stages, while the disseminate stage is not carried out. The research subjects included 31 students and 1 mathematics teacher in grade VII of SMPN 1 Kepahiang. The research instrument consists of validation sheets and questionnaires on the practicality of students and teachers. The study's results showed that the LKPD developed had a validity rate of 87.83% in the very valid category. The results of the practicality test showed that 80.67% of students were in the practical category, and 82.27% of teachers were in the very practical category. These findings show that LKPD, in the context of Ark Culture with a STEAM approach, is suitable as innovative teaching materials to support contextual mathematics learning and improve students' numeracy literacy.